Perppu Pengawasan Hakim Mk Versus Putusan Final Mk - Malik, Malik (Mahkamah Konstitusi Republik Indonesia, 2013)
Government Regulation in Lieu of Law (Perppu) No. 1 of 2013 about the Second Amendment to Act No. 24 of 2003 about Constitutional Court (MK) is an appropriate step to recover public trust to MK after the arrest of non-active Head of MK Akil Mochtar by Corruption Eradication Commission (KPK). Many crucial things are found in Perppu No.1 of 2013 about MK and these are considered as the problem roots but also the efficacious herbs to deter against the replicated corruption practice at MK. One of them is the supervision system of Constitutional Justices. Justices of MK have been once becoming the object of the supervision of Judicial Commission (KY), but the release of the Verdict of Constitutional Court No. 005/PUU-IV/2006 has made the authority of KY to supervise Constitutional Justices degraded into inconstitutional. The verdict of Constitutional Court is final and binding, but it cannot still escape from erga omnes principle, meaning that the verdict is binding in general term and also binding for the object of dispute.